If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 2h = p Solving 2b + 2h = p Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2h' to each side of the equation. 2b + 2h + -2h = -2h + p Combine like terms: 2h + -2h = 0 2b + 0 = -2h + p 2b = -2h + p Divide each side by '2'. b = -1h + 0.5p Simplifying b = -1h + 0.5p
| 9-3c+8s= | | 6y+3=8y-7 | | 5h+6m+3l+f+(h+f)-2m= | | -2+2x=3+5x | | 5(2x-6)=-4 | | -3(6w-4s)= | | y-1=-3+9 | | 5h+6m+3l+f+(2m+c)-h= | | 7x-6y=-20 | | X+Y+X-Y=90 | | 8x+2=9x-4 | | (8x+3)=-4 | | 1n(6-2n)=99 | | 8x+2+9x-4=180 | | Y=0.25x^3-3x | | 5a-19=-74 | | 2(5x)+3c+4(x+c)= | | -2x+34=-48 | | 5k-2(2k+1)=8 | | 7t-(6t-2)=-1 | | (3x+2)=(4x-7) | | -5n-3+6n=2 | | 4x+4-3=5 | | 2(5x+8)=46 | | x^2+12x+36=2s | | 5X^2+54X+81=0 | | 6x-25=4x+15 | | 4(h+f+m)+3(c+f+l)= | | 36x^2-24x+4=6 | | 5y=-2x+16 | | 8+4=(x-1) | | -6j+11=-1 |